Construções geométricas: o estudo da bissetriz em pesquisas produzidas no Brasil de 2010 a 2020 - Pereira, Amanda Correia Teixeira (2021)
This study aims to present the mapping of research produced in Brazil, between the years 2010 to 2020, in relation to geometric constructions and more specifically the bisector of an angle. For the constitution of our research corpus, 18 academic papers found in the CAPES Thesis and Dissertations bank, in Google Scholar and in the PUC Theses and Dissertations bank were selected. The research seeks to answer the following question: "What are the contributions and gaps observed in the research between 2010 and 2020 in Brazil for the teaching of bisector?". Work was found in two major areas: Mathematical Education and Mathematics. As we verified that the works in the area of Mathematics were the majority (14 surveys), we could not exclude them. In this sense, we made the analysis of the research in the area of Mathematics, only considering the mathematical aspect, and in the Mathematics Education researches, the mathematical and didactic aspects were considered. We found that the area of Mathematics Education has given little emphasis to research on geometric constructions and respectively the bisector of an angle in the observed period. The results show that even though the knowledge about bissector is related to na angle, few researches present the definition of angle and most approach angle as a measure, which may imply in understanding the bissector of an angle. Another important point is the lack of justification for the construction of the bisector, as it highlights the characteristics and properties of the mathematical object. Many researches apply activities that emphasize only the construction itself, not exploring problem situations in which the bisector is the solution. Only one research sought in the applied sequence to explore the construction of the bisector in problem situations and to request justifications, concerned with developing in students the perceptual, sequential, discursive and operative apprehensions according to Duval (2004). We suggest that new researches fill these gaps, in order to expand the contributions in Mathematics Education